One-stage operation for superficialization of native radio-cephalic fistula in obese patients. Issue 1 (May 2019) - Okawa, Takao; Murakami, Masaaki; Yamada, Ryo; Tanaka, Satoshi; Mori, Kiyoshi; Mori, Noriko
Purpose: The population of obese patients is increasing in general and also at hemodialysis initiation. For successful cannulation of arteriovenous fistula, the National Kidney Foundation-Dialysis Outcome Quality Initiative guidelines suggest that the required maturation parameters are at a depth of <6 mm. There are several reports describing two-stage superficialization of arteriovenous fistulas in obese cases. Therefore, we investigated the utility and complications of one-stage superficialization of radio-cephalic fistula. Methods: From January 2011 to March 2017, we simultaneously performed forearm radio-cephalic fistula creation and superficialization of the cephalic vein for 10 patients having obesity (body mass index > 30 kg/m 2 ) and deep cephalic vein (>6 mm). Initially, an arteriovenous anastomosis was created at an appropriate site. Subsequently, an 8–10 cm longitudinal skin incision was made along the lateral aspect of the forearm cephalic vein. The cephalic vein was identified and exposed. The cephalic vein was repositioned superficially. Results: The mean age of the patients was 53 years (range: 40–72 years) and the mean body mass index was 40.2 kg/m 2 (33.1–59.7 kg/m 2 ). The cause of renal failure in eight patients was diabetic nephropathy, and in two patients, it was unknown. After the procedure, vein depth became 3.4 mm (1.9–4.6 mm) from 8.2 mm (6.0–13.4 mm). All patients who initiated dialysis underwent successful two-needle cannulation. Primary patency rate was 71.4% at 12 months (two patients underwent percutaneous transluminal angioplasty) and secondary patency rate was 100%. There was one procedure-related complication and delayed wound healing, which was improved by observation without antibiotics. Conclusion: This small series of patients indicates that one-stage superficialization of radio-cephalic fistula is a safe and effective option to start hemodialysis in obese subjects.